Mechanisms of pathophysiology of blood vessels in patients with multiple sclerosis treated with ozone therapy: a systematic review - Ameli, Javad; Banki, Abdolali; Khorvash, Fariborz; Simonetti, Vincenzo; Jafari, Nematollah Jonaidi; Izadi, Morteza (Acta Biomedica Atenei Parmensis, 2019)
Multiple sclerosis (MS) defines as an intricate disease with numerous pathophysiological processes, including: inflammation, demyelination, oxidative stress, axonal damage, and repair mechanisms that interfere in this disease and highly related to the pathogenesis of MS. In parallel, recent studies have shown that the ozone administration could be very useful in treating neurological disorders and inflammatory and degenerative neurological diseases. In this review, we examine the recent literature on the pathophysiology of blood vessels in patients with multiple sclerosis treated with ozone therapy.